Laparoscopic hysterectomy – what does it mean? - Barwijuk, Andrzej Jan; Szymczyk, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2005)
Hysterectomy is the most common gynaecologic operation performed in perimenopausal women. According to increasing interest in endoscopic techniques it is also increasing number of uterus removing procedures with the use of laparoscop. The advantages of this technique are commonly known, one of them is the quick patients’ recovery, which decreases the total therapeutic expenses, also. In broad meaning the term “laparoscopic hysterectomy”comprises particular operations: removing of the uterus, uterus with its cervix, uterus, cervix and adnexa and – in some cases – uterus, cervix, adnexa, with pelvic and periaortal lymph nodes. Basing on data from literature we have undertaken the trial of answer to que-stion – what does the term “laparoscopic hysterectomy” actually mean?